2009
DOI: 10.1350/ijps.2009.11.2.128
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Louisiana Drug Interdiction: Drug Profiling in the Louisiana Justice System

Abstract: Drug profiling by the Louisiana State Police Criminal Patrol Unit (LSP-CPU) and the deputies of the St Martin Parish Sheriff's Office (SMSO) has been through in-depth analyses by Ruiz (2000) and colleagues (Bowling, Ruiz, & Staub, 2008; Ruiz & Woessner, 2006). Ruiz's essential findings support allegations of demographic profiling in traffic arrests on Louisiana's Interstate-10. Also, Ruiz suggested that the most plausible explanation was attributed to the war on drugs specified by Louisiana's asset forfeiture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…NOTE 1. For additional research on racial profiling in St. Martin Parish, see Bowling, Ruiz, & Reynolds, 2008;Ruiz & Lee, 2009;Ruiz & Woessner, 2006;Ruiz, 2000. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…NOTE 1. For additional research on racial profiling in St. Martin Parish, see Bowling, Ruiz, & Reynolds, 2008;Ruiz & Lee, 2009;Ruiz & Woessner, 2006;Ruiz, 2000. …”
Section: Resultsmentioning
confidence: 99%
“…In regard to racial inequalities in the criminal justice system, researchers have concentrated primarily on sentencing (Albonetti, 2002;Hagan, 1974;Johnson, 2003;Kautt & Spohn, 2002;Kleck, 1981;Peterson & Hagan, 1984;Ruiz & Lee, 2009;Spohn, 2000;Spohn & DeLone, 2000;Spohn & Holleran, 2000;Tonry, 1995;Zatz, 1987). However, a review of the literature demonstrated that few studies have focused on judicial decision making in regard to race and bail (Albonetti, 1989;Frazier, Bock, & Henretta, 1980;Goldkamp & Gottfredson, 1979;Mann, 1993;Nagel, 1983;National Minority Advisory Council on Criminal Justice, 1982;Turner, Secret, & Johnson, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…(2005) defines police misconduct as a concept covering 'a heterogeneous set of behaviors, from sleeping on duty, being on duty, being late for work, and using excessive force, to denying the 5th Amendment right to silence, testilying, forging documents, and accepting bribes' (p. 547). Researchers have empirically examined a wide range of issues including demographic profiling (Ruiz & Lee, 2009), corruption (Punch, 2009) and extra-legal factors in police arrests (Lee, Zhang, & Hoover, 2013), among others, to scrutinise the prevalence of misconduct. These studies share the common notion that the sheer amount of contact between citizens and the police, as well as their authority to enforce the law, renders the police a representative public figure.…”
Section: Introductionmentioning
confidence: 99%